Atherectomy with balloon angioplasty compared to balloon angioplasty alone for the treatment of chronic limb threatening ischemia: A national surgical quality improvement program database analysis. (December 2020) - Lam, Alexander; Schwertner, Adam; Katrivesis, James; Fernando, Dayantha; Nelson, Kari; Abi-Jaoudeh, Nadine
Objectives: To compare perioperative outcomes related to atherectomy with percutaneous transluminal angioplasty versus percutaneous transluminal angioplasty alone for the treatment of lower extremity chronic limb threatening ischemia using a national patient database. Methods: Patients with chronic limb threatening ischemia treated with atherectomy and percutaneous transluminal angioplasty or percutaneous transluminal angioplasty alone from 2011 to 2016 in the National Surgical Quality Improvement Program database were identified. Primary outcomes were major adverse limb events (30-day untreated loss of patency, major reintervention, major amputation) and major adverse cardiac events (cardiac arrest, composite outcome of myocardial infarction or stroke). Secondary outcomes included 30-day mortality, length of stay, and any unplanned readmission within 30 days. Multivariate regression analyses were performed to determine independent predictors of outcome. Propensity score matched cohort analysis was performed. A p -value <0.05 was considered statistically significant. Subgroup analyses of femoropopliteal and infrapopliteal interventions were performed. Results: In total, 2636 (77.2%) patients were treated with percutaneous transluminal angioplasty and 778 (22.8%) were treated with atherectomy and percutaneous transluminal angioplasty. Multivariate analyses of the unadjusted cohort revealed no significant differences in major adverse cardiac events or major adverse limb events between the two groups ( p -value >0.05). Subgroup analysis of femoropopliteal interventions demonstrated a significantly decreased likelihood of untreated loss of patency in 30 days in the atherectomy group compared to the percutaneous transluminal angioplasty group (1.1% vs. 2.7%, respectively; p -value = 0.034), which persisted on propensity score matched analysis (1.1% vs. 3.1%, respectively; p -value = 0.026). Conclusion: Atherectomy with balloon angioplasty of femoropopliteal disease provides a significant decrease in untreated loss of patency compared to balloon angioplasty alone.